THE CHOICE OF THE METHOD OF ANESTHESIA FOR PLACENTAL INGROWTH-PROS AND CONS - Василий Николаевич Паличев; Виталий Сергеевич Самоделкин; Нонна Марковна Шибельгут; Светлана Ивановна Елгина; Вадим Гельевич Мозес; Елена Владимировна Рудаева (The Publishing House Medicine and Enlightenment, 2020)
Placenta accreta is one of the two leading causes of bleeding in childbirth and postpartum, and the most common indication for hysterectomy. The frequency of placental ingrowth increases in parallel with the increase in the frequency of caesarean section. The choice of caesarean section and planned hysterectomy is a traditional approach to the treatment of placental ingrowth. Treatment of ingrowth requires coordination between anesthesiologists, obstetricians, radiologists, blood Bank workers and specialized surgical teams. The article describes the experience of doctors of anesthesiology department of the Regional Perinatal Center of the Kemerovo Regional Clinical Hospital named after S.V. Belyaeva. The use of the proposed method of regional anesthesia in the delivery of women with placental rotation can help to avoid maternal complications that are possible with General anesthesia, such as complex and unsuccessful intubations, pulmonary aspiration, intraoperative awakening, the development of chronic pain and increased maternal morbidity. When comparing women with different types of anesthesia, there was a more rare use of blood transfusion, a decrease in blood loss against the background of regional anesthesia. In addition, the ability to maintain intraoperative blood pressure during regional anesthesia has been successful in most caesarean sections under presentation, even under bleeding conditions.